Komunikasi Antarpribadi Pasangan Suami Istri Bahagia Studi Interaksi Simbolik pada Pasangan Suami Istri - Zhafirah, Zena (Universitas Pendidikan Ganesha, 2020)
This study aims to find out verbal symbols in happily married couples and non-verbal symbols in happily married couples. This study uses the theoretical basis of the Symbolic Interaction of George Herbert Mead, Leslie A. Baxter's Dialectical Relationship Theory, and Sandra Petrinio's Communication Management Privacy Theory.This study uses a qualitative approach with a constructivist paradigm and the subject of the study is interpersonal communication among happily married couples in Bandung. The data collection process was obtained through in-depth interviews and direct observation of informants. The results showed that interpersonal communication among happily married couples included two symbols, verbal and non-verbal. Both of them include support of the partner's expectations, giving time to be together with a partner, not easy to be suspicious of a partner, hugging, kissing, and always smiling at a partner and never refusing sex. All of these things will make a happier marriage relationship.